Brukner & Khan's clinical sports medicine - Brukner, Peter, 1952-; Brukner, Peter, 1952-; Khan, Karim (Sydney ; New York : McGraw-Hill, 2012)
Provides an authoritative foundation for clinicians and students in the field of clinical sports medicine in order to help clinicians help patients.
Rev. ed. of: Clinical sports medicine / Peter Brukner and Karim Khan. 3rd ed., c2007.
Written by Peter Brukner, Karim Khan, Roald Bahr, Steven Blair, Jill Cook, Kay Crossley, Jenny McConnell, Paul McCrory, Timothy Noakes.
Includes bibliographical references and index.
Keywords: Sports medicine; Athletic Injuries; Sports Medicine -- methods; Print books